2007
DOI: 10.1016/j.joms.2007.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Characteristics and Treatment Preferences of Oral Surgery Patients

Abstract: Background-Patient preferences for treatment choices may depend on subject characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 14 publications
2
15
0
Order By: Relevance
“…In a study covering 203 patients with jaw fractures it was established that most patients were willing to pay a higher price for restoration or in case there were no scars from the intervention, or if the nerves of the third molar were not devitalized. The clinical characteristics of respondents have no effect on the willingness to pay to the difference of socio-demographic and psychological health characteristics of covered patients [9]. These findings are quite similar to our results so far as recent clinical history did not become a predictor neither for patient preferences nor the willingness to pay for the chosen option.…”
Section: Discussionsupporting
confidence: 90%
“…In a study covering 203 patients with jaw fractures it was established that most patients were willing to pay a higher price for restoration or in case there were no scars from the intervention, or if the nerves of the third molar were not devitalized. The clinical characteristics of respondents have no effect on the willingness to pay to the difference of socio-demographic and psychological health characteristics of covered patients [9]. These findings are quite similar to our results so far as recent clinical history did not become a predictor neither for patient preferences nor the willingness to pay for the chosen option.…”
Section: Discussionsupporting
confidence: 90%
“…In a previous manuscript describing the baseline association between the patient’s preference for treatment (wiring or surgery to repair a fractured jaw) and patient socioeconomic and health-related characteristics, we reported that the predominantly male, unemployed fracture patients demonstrated no significant differences in their SG score than third-molar patients 14. For both groups, however, subjects who chose surgery were willing to accept a greater hypothetical risk of possible nerve damage or scarring than those who chose wiring.…”
Section: Introductionmentioning
confidence: 85%
“…Risk tolerance is often measured using the SG, a health-value utility measure assessing the tradeoff between good outcomes, such as improved health function or appearance, and a serious complication associated with treatment 7,8,10,11, 12, 14,15,16, 17, 18. The strength of the preference for a specific treatment is expressed in terms of the amount of risk the respondent would accept for obtaining improved health function.…”
Section: Methodsmentioning
confidence: 99%
“…However, the samples did not differ on marital status (less than 20% in each sample were married), ethnicity (over 60% were African American in both groups), education (over 60% had at least graduated from high school in both groups), or employment (over 60% were unemployed in both groups). In a follow-up study of similar patients (n=98) with mandibular fractures and a comparison group of third molar patients (n=103), Atchison and colleagues (26) noted that the facial injury patients also reported less perceived social support and smaller social networks.…”
Section: Introductionmentioning
confidence: 99%